The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10461-008-9370-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk Behaviors in Late Middle Age and Older HIV Seropositive Adults

Abstract: Little is known about the sexual behaviors of older adults, although the prevalence of HIV/AIDS is rapidly increasing in this population. As part of a larger multi-site study examining secondary HIV prevention, we recruited from an HIV primary care clinic 210 sexually active HIV positive individuals aged 45 and over (125 men, 85 women) who had engaged in vaginal or anal sex within the past six months. Twenty percent of the participants reported inconsistent use of condoms and 33% had multiple sexual partners d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 33 publications
(24 reference statements)
2
84
1
3
Order By: Relevance
“…11,13 Notable rates of unprotected or inconsistent safe sex-with approximately 20-33% of participants endorsing little or inconsistent condom usehave been documented; factors linked to unsafe sexual behavior included substance use, loneliness, negative affect, and HIV related stigma. [11][12][13] These studies suggest that older adults with HIV are engaging in sexual activity and, as with other populations of individuals with HIV, that a minority may be engaging in high-risk HIV transmission behavior.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…11,13 Notable rates of unprotected or inconsistent safe sex-with approximately 20-33% of participants endorsing little or inconsistent condom usehave been documented; factors linked to unsafe sexual behavior included substance use, loneliness, negative affect, and HIV related stigma. [11][12][13] These studies suggest that older adults with HIV are engaging in sexual activity and, as with other populations of individuals with HIV, that a minority may be engaging in high-risk HIV transmission behavior.…”
mentioning
confidence: 87%
“…10 Given that HIV is largely a sexually transmitted disease, research examining sexual health among HIV-infected individuals has focused primarily on HIV prevention. However, several recent studies have focused on sexual health of older HIV-infected individuals, [11][12][13] with two recent studies showing that approximately 38-50% of men and women over the age of 50 engaged in recent (within the past 3 months) sexual activity. 11,13 Notable rates of unprotected or inconsistent safe sex-with approximately 20-33% of participants endorsing little or inconsistent condom usehave been documented; factors linked to unsafe sexual behavior included substance use, loneliness, negative affect, and HIV related stigma.…”
mentioning
confidence: 99%
“…In their sample, 67% of the respondents self-identified as heterosexual, of those 70% identified as male, 28% female, and 1% transgender. Similarly, Illa et al (2008) reported that 84% of a sample of 125 HIV-positive male participants (aged 45 and older) who attended a large primary-care clinic in Miami, Florida identified as heterosexual and none reported same-sex sexual behaviour.…”
Section: Sexual Orientationmentioning
confidence: 99%
“…Although older men with HIV might report being in a sexual relationship less frequently than do younger and middle-aged men (Önen et al 2010), the number who are in sexually active relationships is far from negligible. Estimates vary across studies from 15% to 47% (Cooperman et al 2007;Elford et al 2008;Illa et al 2008;Lovejoy et al 2008;Önen et al 2010). Recent sexual activity (in the past 3 months) was reported by 27% of HIV-positive men (Önen et al 2010).…”
Section: Sexual Behaviourmentioning
confidence: 99%
See 1 more Smart Citation